Збір та аналіз даних з мережі Honeypot - Русанов, Г. О.; Федюшин, О. І. (ХНУРЕ, 2021)
The given work is dedicated to the means of collecting and analyzing the data received from honeypots. The tools and methods used by hackers to achieve their goals ‒ be it a simple challenge or terrorism acts ‒ are constantly changing and new ones appear that might not be publicly known. The data gathered from these honeypots can later be used for analysis which can give the honeypot owners the clue about these methods and tools used by hackers, to be able to protect the real systems against these kinds of attacks.
Keywords: honeypot; шаблон атаки; структура даних; несанкціоновані дії